Development of GIS-based sebal model for estimation of evapotranspiration in Iraq - Jaber, Hussein Sabah (2017)
A change in weather parameters and climate will result in a significant change in evapotranspiration. Iraq suffers from problems such as reduction in water availability and unpredictable climate change that would affect irrigated agriculture and evapotranspiration. Therefore, estimation of evapotranspiration and standardized measurement are important because evapotranspiration (ET) is the means for exploiting irrigation and irrigation is considered as the backbone of the peasant society. Most of the studies in Iraq depend on traditional methods to estimate evapotranspiration. These conventional methods are not practical for large areas because it is difficult and costly. Therefore, this research aims to use remote sensing (satellite imagery data) and GIS as modern technologies to estimate evapotranspiration. In this research, the proposed model has been developed based on equations of SEBAL by using GIS to make a simplified model for estimation of evapotranspiration automatically that leads to a reduction in cost and time and saves effort. Subsequently, the proposed GIS-based SEBAL model was evaluated with field data by using regression coefficient. The area surrounding the Al-Hindiyah barrage has been selected as a study area because it is one of the most significant water resources in the middle part of Iraq. A series of Landsat OLI (Operational Land Imager) satellite images and climate data of the study area have been collected to determine actual evapotranspiration using the GIS-based model. In addition, actual evapotranspiration has been used to assess irrigation performance based on several indicators and to analyze water balance depending on the curve number method in GIS for the study area, respectively. The results indicate that the proposed GIS-based SEBAL model for estimation of actual evapotranspiration has reasonable agreement with the field data based on the values of coefficient of variance( CoV ) equal to (0.75%, 2.2%, 0.68% and% 2.27% ) indicates that the predicted results of the SEBAL model have high accuracy and consistency. The mean value of the SEBAL model was close to 1.0 (0.99, 0.98, 0.99 and 1.01), which indicated a good correlation between the measured and estimated Et. Therefore, the SEBAL model efficiently estimated the Et. In addition, the results of irrigation performance were poor depending on comparison values of irrigation performance indicator results with recommended values of these indicators. Moreover, the results showed a close agreement between rainfall and runoff based on the value of the CoV values between Q observed/ Q proposed less than Q observed/ Q calculated indicates that the proposed model results have high accuracy and consistency than existing model. Therefore, the proposed model efficiently estimated the runoff. Furthermore, the change of water content (ΔS) for the total study area was observed to have positive values that indicated that there was a percolation of groundwater in the crop root zone that can be used when water was insufficient. This study concludes that the development of the GIS-based SEBAL model for calculating actual evapotranspiration provides an efficient and cost-effective means for estimation of evapotranspiration and it was verified that SEBAL will perform better if it is supported with field data. In addition, there should be a consensus between the period when water is provided from the source and the period when it is needed to increase the irrigation performance. This study provides the possibility of simulating the runoff either on a daily, monthly, seasonal or an annual scale for each rainfall. It can be useful for estimating runoff at places where observed runoff records are not available.